Efeito do ácido rosmarínico sobre as crises epilépticas e alterações comportamentais em diferentes modelos experimentais de epilepsia - Grigoletto, Jéssica (2016)
Epilepsy is a chronic neurological disease characterized by recurrent seizures. Current anticonvulsant drugs are ineffective in nearly one third of patients and may cause significant adverse effects. Rosmarinic acid is a naturally-occurring substance which displays several biological effects including antioxidant, anti inflammatory and neuroprotective activity. Since oxidative stress, inflammation and excitotoxicity play a role in the pathophysiology of seizures, we aimed the present study to test the hypothesis that rosmarinic acid displays anticonvulsant effects in different experimental models. Our results demonstrate that rosmarinic acid at the dose of 30 mg/kg increased the latencies to myoclonic and generalized seizures induced by PTZ and myoclonic seizures induced by pilocarpine. These data were confirmed by encephalographic recordings. Furthermore, the anticonvulsant dose of rosmarinic acid was anxiolytic, since it increased the number of crossings and the time of exploration in the center of open field. In the forced swimming test rosmarinic acid increased the immobility time. In another set of experiments, we evaluated the effects of sub-chronic treatment of rosmarinic acid (30 mg/kg) on epileptic seizures and behavioral changes in epilepsy model induced by pilocarpine. However, the treatment with rosmarinic acid caused no significant changes in the frequency of seizures nor in the behavioral comorbities evaluated. These results probably reflect the GABAergic action of rosmarinic acid, by inhibiting the enzyme GABA- transaminase, since it was anticonvulsant and anxiolytic activity in the acute protocols. However, anticonvulsant effect and/or disease-modifying effects were seen in the chronic model of epilepsy. Further studies are needed to investigate the clinical implications of these findings and their underlying mechanisms.